Analisis Pengaruh Organizational Citizenship Behavior terhadap Kinerja Karyawan dengan Power Distance sebagai Moderator (Studi Kasus pada PDAM Tirta Moedal Kota Semarang) - Oktaviantry, Septi; Masâ€™ud, Fuad (Diponegoro Journal of Management, 2016)
The purpose of this research was to analyze the effect of organizational citizenship behavior on employee performance and analyze the role of power distance as a moderator.This research was conducted at the PDAM Tirta Moedal Kota Semarang. Data collected through distribution of questionnaries to 97 respondents with simpleÂ  random sampling. This research using validity test, realibility test, the classical assumpation test, regression test and MRA (Moderated Regression Analysis) to test moderating variable with SPSS 16.0.The results of this research indicates that organizational citizenship behavior have a positive and significant effect on employee performance. Meanwhle, power distance has a negative significant role on the relationship between organizational citizenship behavior and employee performance. High-power distance have a negative effect role on relationship between organizational citizenship behavior and employee performance.